Pemanfaatan Teknologi Geospasial Untuk Meningkatkan Kompetensi Profesional Guru Geografi SMA - Listyo Yudha Irawan; Aulia Amatullah; Siti Nur Farihah; Alfyananda Kurnia Putra; Nurul Ratnawati; Yuni Auliafani; Isha Pure (Kayon Media, 2025)
Abstract: This study aims to determine the effect of geospatial technology-based Pedagogical Content Knowledge (PCK) training as an effort to improve the professional competence of high school geography teachers. This study uses an ex post facto method, with a qualitative descriptive approach and data collection techniques through field observation, documentation, and pre-test and post-test questionnaires. The results of this study indicate that training in the use of geospatial technology based on Pedagogical Content Knowledge (PCK) has a significant effect on improving teachers' professional competencies, including a comprehensive understanding of the integrative concepts of pedagogy, content, and technology, an increase in the use of geospatial platforms such as Google Earth, Inarisk, and Inageoportal, and the ability to link learning materials with the use of spatial data. This activity is a strategic step in encouraging teachers to become more professional and prepared to face the challenges of the 21st century.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan Pedagogical Content Knowledge (PCK) berbasis teknologi geospasial sebagai upaya peningkatan kompetensi profesionalitas kepada guru geografi tingkat sekolah menengah atas. Penelitian ini menggunakan metode ex post facto, dengan pendekatan deskriptif kualitatif serta teknik pengumpulan data melalui observasi lapangan, dokumentasi dan pemberian kuesioner pre-test dan post-test. Hasil penelitian ini menunjukkan pelatihan pemanfaatan teknologi geospasial berbasis Pedagogical Content Knowledge (PCK) berpengaruh signifikan dalam meningkatkan kompetensi profesional guru, meliputi memahami secara utuh konsep integratif antara pedagogi, konten, dan teknologi, menunjukkan peningkatan dalam penggunaan platform geospasial seperti Google Earth, Inarisk, dan Inageoportal, serta mampu mengaitkan materi pembelajaran dengan penggunaan data spasial. Kegiatan ini menjadi langkah strategis dalam mendorong guru menuju profesionalisme dan kesiapan menghadapi tantangan abad ke-21